Ghana - Promoting Growth, Reducing Poverty - Alam, Asad (World Bank, Washington, DC, 2012)
The policy reforms since 1983 have reduced the fiscal deficit and inflation, helped improve infrastructure services, and shifted relative prices and incentives towards the tradable sector, in general, and towards exports, in particular. The key element of fiscal consolidation up to 1991 was the growth in government revenues, whose share of Gross Domestic Product (GDP) rose from 6 percent in 1983 to 13 percent in 1986 and to 16 percent in 1991. Higher revenues made it possible to reduce the fiscal deficit and, at the same time, increase public investment in infrastructure which had virtually collapsed prior to 1983. Prudent monetary management also led to inflation falling from 123 percent in 1983 to 40 percent in 1986 and 18 percent in 1991. The resulting improvements in macroeconomic stability made it possible for farms and firms to respond to the shift in production incentives induced by the policy reforms. As a result of these reforms, the economy turned around. Although economic activity witnessed its biggest surge during the early years of the Economic Recovery Program (ERP) (5.3 percent annually during 1983-86), aggregate growth has averaged 4.7 percent per annum since 1987. The private sector has made a significant contribution to growth. However, this growth performance has not been uniform across sectors. Agriculture recorded an annual growth rate of only 1.9 percent since 1987 while services have grown at an average annual rate of 7.4 percent over the same period. Merchandise exports and imports have grown faster than GDP and with it, complementary wholesale and retail trade. The share of external trade in GDP increased from about 5 percent in 1983 to 32 percent in 1986, 35 percent in 1991, and 55 percent in 1994.